Left-handed Z-DNA in bands of acid-fixed polytene chromosomes. - Arndt-Jovin, D J (1983)
Antibodies to DNA in the left-handed (Z) conformation bind to acid-fixed polytene chromosomes of both Chironomus thummi and Drosophila melanogaster, as shown by direct and indirect immunofluorescence. Comparison of the phase-contrast, immunofluorescence, and DNA staining patterns shows a predominant localization of the antibody to the regions of high contrast and DNA density, the bands. The immunofluorescence is completely abolished by competition with polynucleotides in the Z conformation but not by those in the B form. DNase but not RNase treatment eliminates the antibody staining. Actinomycin D inhibits binding, whereas mithramycin has no effect. The highly reproducible immunofluorescence patterns obtained with the anti-Z-DNA antibodies demonstrate variations in fluorescence intensity between particular bands, which can be quantitated by laser scanning and photon counting techniques. The telomeric regions and DNA strands associated with end-to-end chromosome linkage and ectopic pairing are exceptionally bright. At saturation, average values of 1 IgG molecule per 3,000 base pairs and 1 per 15,000 base pairs are found in the intensely and weakly staining regions, respectively. An alternative statement is that the left-handed Z-DNA conformation is present at a frequency of 0.02-0.1%. The measured differences reflect variations in the local density of Z-DNA sites and not in the affinity for the specific antibody, which appears to be relatively constant throughout the chromosomes (Kd approximately equal to 10 nM). These observations taken together with results of biophysical studies on the properties of Z-DNA in solution suggest that regions of DNA in the left-handed conformation could be involved in higher-order structural organization of chromosomes and possibly in modulation of their functional state.